Anomalies in curved spacetime at finite temperature - Boschi-Filho, H. [UNESP]; Natividade, C. P. [UNESP] (American Physical Society (APS), 1992)
We discuss the problem of the breakdown of conformal and gauge symmetries at finite temperature in curved-spacetime background, when the changes in the background are gradual, in order to have a well-defined quantum field theory at finite temperature. We obtain the expressions for Seeley's coefficients and the heat-kernel expansion in this regime. As applications, we consider the self-interacting 4 and chiral Schwinger models in curved backgrounds at finite temperature. © 1992 The American Physical Society.